PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN BERPIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA KELAS II SEKOLAH DASAR - Maiko Sabri Martha; Fatkur Rohman; Arin Arianingsih; Nurhanurawati; Kurnia Wati, Ela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and test the effectiveness of Problem Based Learning (PBL) based Learner Worksheet (LKPD) in improving critical thinking skills of grade II elementary school students on flat building material. The research was conducted at SDN 2 Sawah Lama with 25 students as subjects. The research method used is Research and Development (R&D) with the ADDIE model which includes analysis, design, development, implementation, and evaluation stages. The evaluation instrument was in the form of pretest and posttest with a total of 18 items (10 multiple choice, 5 essays, and 3 fillings), which were analyzed statistically through paired sample t-test. The validation results showed that the LKPD was declared very valid by the experts. Analysis of learning outcomes showed a significant increase in critical thinking skills, indicated by the average pretest score of 53.2 and posttest of 82.1 (p < 0.05). In addition, there was an increase in the ability category from “low” and “sufficient” to “good” and “very good” in most students. This finding shows that the application of PBL-based LKPD is not only effective in improving learning outcomes, but also able to foster critical thinking skills since elementary school level. This model is very relevant to the project-based learning approach and the strengthening of the Pancasila Student Profile in the Merdeka Curriculum.